2021
DOI: 10.1080/10942912.2021.1977657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fatty acids, phenolics and bioactivities of spent coffee grounds prepared from Vietnamese coffee

Abstract: Spent coffee ground (SCG) is a residue released during coffee brewing. Disposal of SCG is able to lead to a loss of bioactive constituents and have a negative impact upon the environment. This study aimed to explore fatty acids, bioactive phenolics, antioxidant and anti-aging potentials of SCG samples obtained from coffee shops in Ho Chi Minh city, Vietnam. The oil content of the SCG samples ranged from 6.3 to 10.5%, and linoleic (43%), palmitic (33.4%) and oleic (11%) acids were identified as major constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…The focus on chlorogenic acid is due to its potential health bene ts described in previous studies, including free radical scavenging capacity, antiin ammatory, antidiabetic, and anticancer effects 20 . Cinnamic acid, which is predominant in the present study in agreement with Vamanu et al 21 , has generally been reported to be phenolic constituents in SCG in previous research but in much lower concentrations with respect to the extraction technique 22 . As explained above, the variations might be due to many reasons, including solvent, solvent/sample ratio, extraction time, extraction method, and temperature.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The focus on chlorogenic acid is due to its potential health bene ts described in previous studies, including free radical scavenging capacity, antiin ammatory, antidiabetic, and anticancer effects 20 . Cinnamic acid, which is predominant in the present study in agreement with Vamanu et al 21 , has generally been reported to be phenolic constituents in SCG in previous research but in much lower concentrations with respect to the extraction technique 22 . As explained above, the variations might be due to many reasons, including solvent, solvent/sample ratio, extraction time, extraction method, and temperature.…”
Section: Resultssupporting
confidence: 92%
“…Compared to ethanol and methanol, water was reported as the most e cient solvent for the extraction of gallic acid; therefore, it was not always detected in SCGs 24 . However, gallic acid was identi ed in the current study with a median concentration, maybe due to the detection and quanti cation sensitivity of the analysis 22 . On the other hand, coumaric (0.16 µg/g), gentisic (0.26 µg/g), and ferulic (0.37 µg/g) acids were the lowest compared to the identi ed constituents, which are in agreement with Angeloni et al 25 (Table 1).…”
Section: Resultsmentioning
confidence: 69%
“…S1 . The main phenolic compounds, such as chlorogenic acid, ferulic acid, caffeic acid, and p-coumaric acid, could be obtained by extraction of SCG with water 47 , 48 . In green synthesis, phenolic compounds could release electrons to reduce silver ions and Ag cation reduction could be coupled with the oxidation of the hydroxyl group of phenolic compounds 44 , 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Phenolics in the CT samples were determined on a Shimadzu LC-2030C high performance liquid chromatography system equipped with a diode-array detector (HPLC-DAD). The analysis was carried out on a C18 reverse-phase column (250 × 4.6 mm, 5.0 µm particle size), based on the method previously described by Vu et al (2021). 17 The mobile phase comprised methanol (A) and 1% formic acid in water (B).…”
Section: Determination Of Phenolicsmentioning
confidence: 99%
“…The analysis was carried out on a C18 reverse-phase column (250 × 4.6 mm, 5.0 µm particle size), based on the method previously described by Vu et al (2021). 17 The mobile phase comprised methanol (A) and 1% formic acid in water (B). The gradient profile of the mobile phase was: 25% A for 3 min, 25 -40% A for 5 min, hold 40% A for 4 min, 40 -60% A for 4 min, hold 60% A for 4 min, 60 -80% A for 3 min, hold 80% A for 3 min, 80% -85% A for 4 min and hold 80% for 2 min, then reduced to 25% A at the 35 th min.…”
Section: Determination Of Phenolicsmentioning
confidence: 99%